Evaluation of the performance of two neutral oral contrast agents in computed tomography enterography: A randomized controlled trial - Zheng, Meng Qi; Zeng, Qing Shi; Yu, Yong Quan; Ji, Rui; Li, Yue Yue; Zhang, Ming Ming; Sun, Yi Ning; Li, Li Xiang; Zuo, Xiu Li; Yang, Xiao Yun; Li, Yan Qing (Journal of digestive diseases, 2020)
Objective To compare the performances, tolerability and acceptability of mannitol and polyethylene glycol (PEG) as oral contrast agents in patients undergoing computed tomography enterography (CTE). Methods Patients aged 18‐75 years indicated for CTE were randomized to receive either mannitol or PEG as contrast agents. The coronal reconstructed images of each abdominal quadrant were assessed for maximum distention, proportion of distended bowel loops, presence of inhomogeneous contents and visibility of the small bowel wall. Overall subjective imaging quality assessment and patients’ tolerability and acceptability were recorded. Results Seventy patients were enrolled and randomized into two groups. In the per‐protocol analysis, no significant differences in imaging quality was found in bowel distention maximum diameter, wall visibility and intestinal homogeneity (all P > 0.05). The mean nausea score was lower in the mannitol group (0 [0‐0] vs 1.0 [0‐3.0], P < 0.001). Mannitol was superior to PEG in taste (9.0 [8.0‐10.0] vs 7.0 [5.0‐8.0], P < 0.001), patients’ willingness to reuse the drug (9.0 [8.0‐10.0] vs 8.0 [7.0‐9.0], P = 0.036), satisfaction (9.0 [8.0‐10.0] vs 8.0 [7.0‐9.0], P = 0.022) and ease of completion (9.0 [8.0‐9.3] vs 8.0 [6.5‐9.0], P = 0.030). Conclusions Both mannitol and PEG provided good bowel distention and visualization of the bowel wall. However, mannitol was significantly superior to PEG in patients’ tolerability and acceptability.